Leaf growth and osmotic adjustment of subterranean clover under drought - Gulías J.; Fernández G.A.; Medrano H. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
The drought effect on osmotic adjustment and leaf expansion was analysed in four subterranean clover cultivars. Both parameters showed wide genetic variability. The two genotypes with highest osmotic adjustment in expanding leaves also showed the lowest reduction in leaf expansion rate.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)